2011
DOI: 10.1007/s12029-011-9292-y
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Cell Cycle Regulators P21 and P27 as Predictors of Disease Outcome in Colorectal Carcinoma

Abstract: p27 expression seems to be more powerful than p21 expression in providing useful prognostic information in CRC, particularly in predicting the patients at high risk for recurrent disease. Larger cohort and longer follow-up are needed to fully elucidate the value of p27 (and p21) as independent predictors of disease outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 35 publications
4
13
0
1
Order By: Relevance
“…It is known that p27 expression is lower in a series of human cancers, including CRC and breast and lung cancer (20,31,32). In the present study, 32.79% of tumors showed lower or depleted p27 expression, in agreement with the report of Al-Maghrabi et al (18). The present study found that there were no significant correlations between the loss of p27 expression and gender, age and depth of invasion.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…It is known that p27 expression is lower in a series of human cancers, including CRC and breast and lung cancer (20,31,32). In the present study, 32.79% of tumors showed lower or depleted p27 expression, in agreement with the report of Al-Maghrabi et al (18). The present study found that there were no significant correlations between the loss of p27 expression and gender, age and depth of invasion.…”
Section: Discussionsupporting
confidence: 93%
“…This observation is in agreement with the study by Shapira et al (33), who reported low p27 levels associated with poorly-differentiated tumors, but not with age, gender and clinical stage in CRC. However, Al-Maghrabi et al (18) showed that p27 expression was only associated with depth of invasion and not with tumor grade, lymph metastasis and clinical stage in CRC. Although p27 may be significantly associated with tumor invasiveness characteristics, including grade, depth of invasion and clinical stage, the prognostic value of p27 remains controversial.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The degree of p21 immunoreactivity is assumed to reflect the degree of expression of the normal p21 gene and serves as a useful tool for assessing its function (Goan et al, 2005). Its expression has been reported to be increased in cutaneous squamous cell carcinoma (Stoyanova et al, 2012), non-small-cell lung carcinoma (Groeger et al, 2000), head and neck cancer (Kapranos et al, 2001), and hepatocellular carcinoma (Zhang et al, 2009) but decreased in colorectal carcinoma (Al-Maghrabi et al, 2012) and ovarian carcinoma (Yan et al, 2004). Its expression has been reported to be increased in cutaneous squamous cell carcinoma (Stoyanova et al, 2012), non-small-cell lung carcinoma (Groeger et al, 2000), head and neck cancer (Kapranos et al, 2001), and hepatocellular carcinoma (Zhang et al, 2009) but decreased in colorectal carcinoma (Al-Maghrabi et al, 2012) and ovarian carcinoma (Yan et al, 2004).…”
Section: Discussionmentioning
confidence: 99%